Impact of dental caries on the quality of life in children of 11 to 12 years of the Dolores J Torres Educational Unit, Sagrario Parish, Cuenca. - Zhunio Ordoñez, Karla (2020)
Objective: The objective of this work was to establish the impact of dental caries and the prevalence of oral conditions on daily performance in the quality of life in 11 and 12 year old schoolchildren of the Dolores J. Torres Educational Unit, Sagrario Parish, Cuenca, 2015.Materials and Methods: This study is descriptive, observational, cross-sectional. The universe was 115 schoolchildren, of which a sample of 90 participants with an average age of 11.24 + 0.42 (DT) was taken, 100% were female,   the data were collected through an interview, using the OIDP instrument Spanish version. Results. 100% of the girls showed one or more of an impacted performance. The oral problem that most affects is bad breath followed by sensitive teeth and decayed teeth, which have been annoying at the time of eating or cleaning the mouth. 73.3% of schoolchildren have 1 to 4   seals. 36.7% of girls are free of tooth decay. One of the 90 participants has lost a permanent dental piece. The difference of girls who had or did not decay only varies at the time of rest and in school work. Conclusions: The prevalence of the impact of oral conditions on the HRQL of schoolchildren was very high (100%), which means that all schoolchildren showed at least an impacted performance, the highest being: eating and smiling.